Biologic regulation of physical activity - Rowland, Thomas W. (Human Kinetics, 2017)
Biologic Regulation of Physical Activity provides readers with a cutting-edge perspective of underlying issues that may contribute to the obesity epidemic. It offers evidence of a biologic regulator affecting physical activity and explores implications of such biologic control on activity.